Effects of high intensity cycling interval training on endurance performance in ice-hockey players - Martinmäki, S. (2013)
Ice-hockey has changed considerably during the last few decades. Sport has become quicker, more physical and demanding for players. High levels of aerobic and anaerobic performance are crucial. Training programs and endurance training are expected to cause beneficial changes in aerobic performance which may ultimately lead to enhanced on-ice performance in ice-hockey players. Advanced and optimized training programs are developed to find optimal training intensity, load and recovery. The purpose of this study was to find out how effective a carefully planned high intensity cycling training program is for endurance performance in ice-hockey players. 24 competitive ice-hockey players trained for six weeks in three different groups. The cycling training group (n=8, 23.1 ± 1.2 yrs., 178.9 ± 4.9 cm, 78.9 ± 6.0 kg) trained endurance with high intensity cycling total of ten training sessions. The running group (n=8, 25.1 ± 1.2 yrs., 181.3 ± 6.4 cm, 83.2 ± 11.0 kg) trained endurance with high intensity running total of ten training sessions. The team training group (n=8, 19.8 ± 0.7 yrs., 182.3 ± 5.8 cm, 86.6 ± 8.9 kg) trained endurance according to the team training program. The cycling group resulted in significant changes in cycling time (5.9 %, p<0.01) and in maximal power output (5.8 %, p<0.05) in maximal cycle ergometer test. The running group did not result in significant changes in aerobic performance measured with maximal cycle ergometer test. The team training group resulted in a significant change in cycling time (2.8%, p<0.05). Differences in changes regarding cycling time were significant between the cycling and running groups (p<0.05) as well as between the team training and running groups (p<0.05). The cycling group improved performance in all strength tests. It is suggested that aerobic training in ice-hockey players can be optimized with a carefully planned high intensity cycling interval training program which is based on the individual training intensities determined from heart rate reserve without any concurrent strength interfering effects. Optimized individual training programs allow more time for highquality training of the other important components in ice-hockey performance.